THE EFFECT OF AMMONIUM SULPHATE (ZA) FERTILIZER CONCENTRATION ON THE GROWTH OF MICROALGA POPULATION (Nannochloropsis oculata) - Fery, Rony Andes; Nasution, Syafruddin; Siregar, Sofyan Husein (Asian Journal of Aquatic Sciences, 2020)
This research was conducted from 24 June to 6 July 2019 in the Regional Technical Implementation Unit of the Seawater and Brackish Aquaculture Fisheries Center (UPTD BPBALP Teluk Buo), West Sumatra. This study aim to determine the effect of Ammonium Sulfate ((NH4)2SO4) with different concentrations on the growth rate of Nannochloropsis oculata microalgae population. The method used in this study is an experimental method using a completely randomized design (CRD) one factor, namely ZA fertilizer concentration. There were 5 (five) levels concentration tested, namely 0 ml/L (control treatment), 30 ml/L (treatment A), 40 ml/L (treatment B), 50 ml/L (treatment C), and 60 ml/L (treatment D) total of 15 treatment units. The test organism in this study was N. oculata. The container used is a glass jar (2 liter capacity). The test parameters in this study are the maximum cell population density achieved during 5 days of maintenance (120 hours), relative growth, self-doubling time and specific growth rate during the exponential growth phase. The results of this study indicate that the best concentration of ZA fertilizer for cell population growth is 40 ml/L, followed by a concentration of 30 ml/L, a concentration of 50 ml/L, a concentration of 60 ml/L and the lowest at a concentration of 0 ml/L (control).